2012
DOI: 10.1111/jth.12004
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate binds to human von Willebrand factor in vivo and modulates its interaction with glycoprotein Ib

Abstract: Summary. Background: Polyphosphate, a phosphate polymer released by activated platelets, has recently been described as a potent modulator of blood coagulation and fibrinolysis. In blood plasma, polyphosphate binds to and alters the biological functions of factor XII, fibrin(ogen), thrombin and factor VII activating protease. Objectives: The aim of the present study is to investigate whether polyphosphate also binds to von Willebrand factor (VWF) and alters some of its activities. Methods/Results: When studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…They are also known to inhibit the activity of tissue factor pathway inhibitor by stimulating the activation of FV, 19 stabilize fibrin clots, 19 and modulate the interaction between von Willebrand factor and the platelet receptor glycoprotein1b. 49 PdSP15 proteins inhibit the activation of FXII and FXI, as well as the cleavage of FXI by FXIIa or thrombin, and would be expected to inhibit any anionic surface–mediated reaction. Mast cell proteases such as tryptase occur as heparin complexes, with heparin being essential for stabilization of the tetrameric structure of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…They are also known to inhibit the activity of tissue factor pathway inhibitor by stimulating the activation of FV, 19 stabilize fibrin clots, 19 and modulate the interaction between von Willebrand factor and the platelet receptor glycoprotein1b. 49 PdSP15 proteins inhibit the activation of FXII and FXI, as well as the cleavage of FXI by FXIIa or thrombin, and would be expected to inhibit any anionic surface–mediated reaction. Mast cell proteases such as tryptase occur as heparin complexes, with heparin being essential for stabilization of the tetrameric structure of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Although fibrinogen binding to integrin a IIb b 3 is normal in Ip6k1 2/2 platelets, it is possible that vWF function is compromised due to lowered levels of polyP. 12 Trafficking of cargo to dense granules is dependent on the adaptor protein complex AP3, the function of which is compromised in IP6K1 knockout MEFs. 29 It is possible that the decrease in platelet polyP in Ip6k1 2/2 mice is secondary to an AP3-dependent trafficking defect.…”
Section: Analysis Of Platelet Functionmentioning
confidence: 99%
“…49 PolyP also reversed a defect in vWF-dependent platelet agglutination in patients of type I von Willebrand disease. 12 Hermansky-Pudlak syndrome is a form of dSPD in which patients display dysfunctional biogenesis of lysosomerelated organelles including platelet dense granules, leading to prolonged bleeding time in addition to other clinical features such as albinism. Lengthened plasma clotting time in Hermansky-Pudlak syndrome patients can be rescued by the addition of polyP.…”
Section: Ip6k1 Participates In Hemostasis 1483mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruiz et al [7] reported that platelet dense granules are essentially acidocalcisomes, containing abundant polyP inside the granules. Platelet alpha granules also contain polyP, but at markedly lower concentrations [30]. Platelet polyP is smaller and much less heterodisperse than microbial polyP, with lengths of approximately 60 to 100 phosphate units [7, 21].…”
Section: Polyp In Plateletsmentioning
confidence: 99%